2022
DOI: 10.22201/fo.1870199xp.2008.12.1.15690
|View full text |Cite
|
Sign up to set email alerts
|

Rasgos Morfológicos Dentales Coronales en dentición temporal y permanente: Distancia biológica entre tres grupos indígenas del Amazonas Colombiano

Abstract: Objetivos: Determinar la frecuencia y variabilidad de doce rasgos morfológicos dentales coronales (Winging, incisivos centrales y laterales en pala, doble pala, cúspide de Carabelli, patrón cuspídeo, número de cúspides, cresta distal del trigónido, pliegue acodado, protostílido, cúspide 6 y cúspide 7), en dientes temporales (ui1/ui2/um2/lm2) y permanentes (UI1/UI2/ UM1/LM1), para comprender la influencia étnica y la distancia biológica de tres grupos indígenas del Amazonas Colombiano. Material y métodos: Se re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Rodriguez (2003) has used this trait to discriminate between European populations and Asian populations, including Amerindians. Different studies on Colombian indigenous populations have identified high frequencies of the shovelshaped incisor trait in groups that have remained relatively isolated, while the decrease in their expression (grades 1 to 3) could be associated with mixed origin with European and Afro-descendant mixed origin groups Aragón et al, 2008;Díaz et al, 2014).…”
Section: Obtained Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodriguez (2003) has used this trait to discriminate between European populations and Asian populations, including Amerindians. Different studies on Colombian indigenous populations have identified high frequencies of the shovelshaped incisor trait in groups that have remained relatively isolated, while the decrease in their expression (grades 1 to 3) could be associated with mixed origin with European and Afro-descendant mixed origin groups Aragón et al, 2008;Díaz et al, 2014).…”
Section: Obtained Resultsmentioning
confidence: 99%
“…One of the most interesting traits to study in contemporary Colombian populations is Carabelli's trait, which is considered a European trait with great discriminating power between mixed, Afro-Colombian, and indigenous Colombian groups. However, through different studies, it has been possible to understand that the dichotomous expression (absence/presence) of the ASUDAS reference plaque should not be associated with ethnically mixed origin (Aragón et al, 2008;Díaz et al, 2014, Zúñiga et al, 2016, due to the fact that indigenous Colombian populations have been characterized by presenting fossa expressions in intermediate degrees, which are considered present in the gradation, so they have been recognized as a characteristic pattern of all Amerindians . In a study that grouped different contemporary populations of southwestern Colombia, it was found that mixed groups presented fossa expressions, Y depressions, and small cusps.…”
Section: Obtained Resultsmentioning
confidence: 99%
“…Thus a sample was constituted with 18 Embera indigenous from Alto Baudo (Choco) -12 women and 6 men- (Moreno et al, 2016), 25 Caucasoid mestizos from Cali (Valle del Cauca) -13 women and 12 men- (Aguirre et al, 2006), 156 African descents from Cali (Valle del Cauca) -79 women and 77 men- (García et al, 2015), 60 Misak indigenous from Silvia (Cauca) -34 women and 26 men- (García et al). 100 Nasa indigenous from Morales (Cauca) -62 women and 38 men- (Díaz et al, 2014), and 100 indigenous from Leticia (Amazonas) -56 women and 44 men- (Aragón et al, 2008). The models were taken into account whose second primary molars and first permanent molars present without wear or fracture (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the frequency and variability of TCMTs, human populations can be associated with geographical distributions, and different researchers have ethnographically classified human beings in complex populations from dental morphology. [25,26] The first of these complexes was defined by Hanihara in 1966 [27] as the mongoloid dental complex, which brings together different populations from East Asia that are consistent characteristic of the maxillary molars. Thus, it is reasonable to conclude that the Carabelli trait is significant in the evolution of man and possibly in different racial groups.…”
Section: Hypoconementioning
confidence: 99%